Brain opioid segments and striatal patterns of dopamine release induced by naloxone and morphine. Issue 4 (7th December 2021) - Shokri‐Kojori, Ehsan; Naganawa, Mika; Ramchandani, Vijay A.; Wong, Dean F.; Wang, Gene‐Jack; Volkow, Nora D.
Abstract: Opioid receptors are expressed throughout the brain and play a major role in regulating striatal dopamine (DA) release. Clinical studies have shown that naloxone (NAL, a nonspecific opioid antagonist) in individuals with opioid use disorder and morphine (MRP, a nonspecific opioid agonist) in healthy controls, resulted in DA release in the dorsal and ventral striatum, respectively. It is not known whether the underlying patterns of striatal DA release are associated with the striatal distribution of opioid receptors. We leveraged previously published PET datasets (collected in independent cohorts) to study the brain‐wide distribution of opioid receptors and to compare striatal opioid receptor availability with striatal DA release patterns. We identified three major gray matter segments based on availability maps of DA and opioid receptors: striatum, and primary and secondary opioid segments with high and intermediate opioid receptor availability, respectively. Patterns of DA release induced by NAL and MRP were inversely associated and correlated with kappa (NAL: r (68) = −0.81, MRP: r (68) = 0.54), and mu (NAL: r (68) = −0.62, MRP: r (68) = 0.46) opioid receptor availability. Kappa opioid receptor availability accounted for a unique part of variance in NAL‐ and MRP‐DA release patterns (Δ R 2 >0.14, p <.0001). In sum, distributions of opioid receptors distinguished major cortical and subcortical regions. Patterns of NAL‐ and MRP‐induced DA release had inverse associations with striatal opioid receptor availability. Our approach provides a pattern‐based characterization of drug‐induced DA targets and is relevant for modeling the role of opioid receptors in modulating striatal DA release. Abstract : We characterized the brain‐wide distribution of opioid receptors and, within the striatum, studied their association with drug‐induced dopamine release patterns. There was highest opioid receptor availability in a brain primary opioid segment including frontal, temporal, limbic, thalamic, cerebellar vermis, and periaqueductal gray regions. Patterns of dopamine release induced by naloxone and morphine were inversely related and were both associated with mu and uniquely with kappa opioid receptor availability. The data revealed major brain opioid segments and showed that striatal DA release patterns were related to the pharmacology of opioid drugs.